Host Immunity to Clostridium difficile PCR Ribotype 017 Strains - Jafari, Nazila V. (Infect Immun, 2014)
Clostridium difficile is an important nosocomial pathogen and the leading cause of antibiotic-associated diarrhea. Multilocus sequence typing indicates that C. difficile strains belong to five distinct genetic clades encompassing several PCR ribotypes (RT). Since their emergence in 2003, hypervirulent RT027 strains have been a major focus of research; in contrast, our current understanding of RT017-mediated disease pathogenesis lags far behind. In this study, we aimed to characterize host immunity to CF5 and M68, two genetically well-defined RT017 strains. Both strains engaged with host Toll-like receptor 2/6 (TLR2/6), TLR2-CD14, and TLR5 to similar extents in a model cell line. Despite this, CF5 mediated significantly greater dendritic cell (DC) interleukin-12 (IL-12), IL-27, and IL-10 immunity than M68. Both strains elicited similar IL-1β mRNA levels, and yet only M68 caused a marked increase in secretory IL-1β. A CF5 cocultured-DC cytokine milieu drove an equipotent Th1 and Th17 response, while M68 promoted greater Th17 immunity. Human gastrointestinal ex vivo cytokine responses to both strains were characterized. Taken together, our data suggest that C. difficile strains mediate overlapping and yet distinct mucosal and DC/T cell immunity. Finally, toxin-driven IL-1β release supports the hypothesis that this cytokine axis is a likely target for therapeutic intervention for C. difficile infection.